2014
DOI: 10.14366/usg.13022
|View full text |Cite|
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of thyroid gland with local recurrence: ultrasonographic and computed tomographic findings

Abstract: Primary squamous cell carcinoma of the thyroid gland (PSCCT) is a rare malignancy that presents with advanced disease and poor prognosis. It is difficult to diagnose PSCCT in its early stage because of its rarity and lack of typical imaging findings. We experienced an elderly woman with PSCCT confirmed by surgery. Although preoperative fine-needle aspiration revealed no malignancy, surgical resection was performed because the ultrasonogram showed diffuse microcalcifications, which suggested malignancy, and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Some 17 publications with 48 cases without complete work-up, including CT-scan, panendoscopy, immunohistochemistry and double citations were excluded [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. Finally, 35 papers and ours reporting on 50 patients were available for analysis [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58].
Fig. 2The flow chart of identified studies.
…”
Section: Results Of Systematic Literature Reviewmentioning
confidence: 99%
“…Some 17 publications with 48 cases without complete work-up, including CT-scan, panendoscopy, immunohistochemistry and double citations were excluded [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. Finally, 35 papers and ours reporting on 50 patients were available for analysis [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58].
Fig. 2The flow chart of identified studies.
…”
Section: Results Of Systematic Literature Reviewmentioning
confidence: 99%
“…In this case, positivity for CK5/6 and EMA and negativity for TTF-1 and TG expression predicted squamous cell carcinoma derivation and excluded the possibility of these common tumors (3,21). Further positivity for p63 and Ki67 expression as poor prognostic markers was associated with its poorly differentiated tumor grade (7,22).…”
Section: Discussionmentioning
confidence: 58%
“…To our knowledge, no reports on CEUS imaging findings of ThyPSCC have appeared in the English-language literature. According to Jang et al (7), ThyPSCC showed a large heterogeneously enhancing thyroid mass with a large central non-enhancing portion on enhanced CT, which corresponded well with the squamous cell carcinoma portion with a necrotic portion in pathologic staining. Because of the rapid growth of squamous tumor cells, relatively few interstitial blood vessels in tumors were related to the low peak signal intensity and low AUC on CEUS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The final diagnosis of PSCT should be made after the comprehensive consideration based on the combination of clinical, radiographic, pathologic and immunohistochemical results. Radiologically, PSCT is lack of specific findings [2,7]. Immunohistochemistry is essential for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%